Rhigognostis senilella (Zetterstedt, 1839) and R. marmorosella (Wocke, 1849): two valid species distinguishable in genitalia (Lepidoptera, Plutellidae) - Baraniak, Edward (Zootaxa, 2016)
Rhigognostis senilella was described from Greenland over 150 years ago by Zetterstedt. Its historical range of distribution included also mountains in most of Europe. It was classified in Europe as a boreal-alpine zoogeographic element. Analysis of the structure of the male and female genitalia over its historical range shows that two distinct species are present. The range of R. senilella (Zetterstedt, 1839) is limited to Greenland and Iceland, whereas the mountains of Europe are inhabited by R. marmorosella (Wocke, 1849). The paper includes keys to distinguish these two species, one based on external characters, another on male or female genitalia.